Prediktabilitas Ajudikasi Konstitusional: Mahkamah Konstitusi dan Pengujian Undang-Undang - Titon Slamet Kurnia (The Constitutional Court of the Republic of Indonesia, 2016)
There is a strong commitment that constitutional adjudication should be more predictable. As a principle, what has been rightly decided in the past should be the law for the future cases or controvercies. This article makes a substantial critics directed to the constitutional court of decision Number 14/PUU-XI/2013 on the constitutionality of presidential election rules. This articles argues that the decision shows that predictability is still a serious matter in constitutional adjudication in Indonesia. The author then recommends that to be more predictable the constitutional of court should make a judicial tradition for respecting its past right decisions.